Differential expression of miRNAs in a human developing neuronal cell line chronically infected with Zika virus. Issue 1 (1st January 2021) - Bagasra, Omar; Shamabadi, Narges Sadat; Pandey, Pratima; Desoky, Abdelrahman; McLean, Ewen
ABSTRACT: Zika virus (ZIKV) is a serious public health concern that may lead to neurological disorders in affected individuals. The virus can be transmitted from an infected mother to her fetus, via mosquitoes, or sexually. ZIKV infections are associated with increased risk for Guillain-Barré syndrome (GBS) and congenital microcephaly in newborns infected prenatally. Dysregulations of intracellular microRNAs (miRNAs) in infected neurons have been linked to different neurological diseases. To determine the potential role of miRNAs in ZIKV infection we developed a chronically infected neuroblastoma cell line and carried out differential expression analyses of miRNAs with reference to an uninfected neuroblastoma cell line. A total of 3192miRNAs were evaluated and 389 were found to be upregulated < 2-fold and 1291 were downregulated < 2-fold. In particular, we determined that hsa - mir-431-5p, hsa-mir-3687, hsa-mir-4655-5p, hsa-mir-6071, hsa-mir-762, hsa-mir-5787, and hsa-mir -6825-3p were significantly downregulated, ranging from -5711 to -660-fold whereas, has-mir-4315, hsa-mir-5681b, hsa-mir-6511a-3p, hsa-mir-1264, hsa-mir-4418, hsa-mir-4497, hsa-mir-4485-3p, hsa-mir-4715-3p, hsa-mir-4433-3p, hsa-mir-4708-3p, hsa-mir-1973 and hsa-mir-564 were upregulated, ranging from 20-0.8-fold. We carried out target gene alignment of these miRNAs with the ZIKV genome to predict the function of the differentially expressed miRNAs and their potential impact on ZIKV pathogenesis. These miRNAs might prove useful as novel diagnostic or therapeutic markers and targets for further research on ZIKV infection and neuronal injury resulting from ZIKV infectivity in developing fetal brain neurons.